Real-time technical support for guiding remotely ICD/CRT-D implantation - Curcio, Antonio; Romano, Letizia R.; Augusto, Florinda M.; Canino, Giovanni; Coluccio, Elisa; Polimeni, Alberto; Indolfi, Ciro (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIn the electrophysiologic (EP) lab, technical support for implantable cardioverter/defibrillators (ICD) and cardiac resynchronization therapy (CRT-D) procedures is often limited by the availability and costs of field clinical specialist (FCS) bioengineers.MethodsThis study explores the viability of using remote support through an internet-based platform for ICD and CRT-D implantation procedures, aiming to enhance efficiency and overcome geographical or pandemic-related barriers. After preclinical phases, thirty patients underwent ICD/CRT-D guided either remotely or with on-site FCS implantation at two primary cardiac care centers, with ten procedures guided remotely and twenty cases with on-site FCS.ResultsAll procedures in both study arms were successfully completed (100% of cases). Procedural time was shorter in the telemedicine group (P = 0.031). Although fluoroscopic time was slightly reduced in the remote guided group, the difference did not reach statistical significance (P = 0.5). No major adverse events occurred.ConclusionThe study demonstrates the feasibility of remotely supported ICD and CRT-D implantation procedures.